2009
DOI: 10.1186/1475-9276-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Trend in geographic distribution of physicians in Japan

Abstract: Background: Since the late 1980s, the policy of the Japanese government regarding physician manpower has been to decrease the number of medical students. However, the shortage of doctors in Japan has become a social problem in recent years. The aim of this study was to compare the numbers of physicians in Japan between 1996 and 2006 and the trends in distribution of physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 12 publications
5
137
4
2
Order By: Relevance
“…The Gini coefficient is generally used to measure the geographical maldistribution of physicians [6][7][8][9][10][11][12][13][14][15] and municipal population is usually used for weighting. The present study calculated the Gini coefficient using population, as well as the Gini coefficient using demand for medical services, measured by the age structure of each municipality.…”
Section: Gini Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gini coefficient is generally used to measure the geographical maldistribution of physicians [6][7][8][9][10][11][12][13][14][15] and municipal population is usually used for weighting. The present study calculated the Gini coefficient using population, as well as the Gini coefficient using demand for medical services, measured by the age structure of each municipality.…”
Section: Gini Coefficientmentioning
confidence: 99%
“…[7][8][9][10][11] Toyabe calculated the Gini coefficient, Atkinson index and Theil index across municipalities from 1996 to 2006 for university hospital physicians, other hospital physicians and clinic physicians, and found that for other hospital and university hospital physicians each index had increased after 2004, indicating that the new postgraduate program had exacerbated the geographical maldistribution of physicians. [12] Sakai et al measured pediatrician distribution across municipalities by a 0-14 population-weighted Gini coefficient, and reported that the Gini coefficient had increased in urban prefectures after 2004. [13] Tanihara et al calculated the Gini coefficient for physicians in the secondary tiers of medical care as defined by the Medical Service Law and related legislation (medical administration areas which cover ordinary medical services such as general operations and emergency medicine) from 1998 to 2008, and reported the Gini coefficient decreased until 2006 but increased after 2006.…”
Section: Introductionmentioning
confidence: 99%
“…22 and South Africa 23 also face this problem in different ways. For example, studies show that while the number of physicians has increased in Japan but the inequality index has also increased every year 24 . In addition, nearly 50 percent of the health care providers in Nicaragua are concentrated in the capital, which has only one-sixth of the country's population 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The study findings revealed that the manpower distribution has been relatively equal in the provinces of Iran; the manpower resources have always been an essential element in the health system and played the most important role in providing health services (18); thus, the lack of manpower may create a great obstacle against the goals of organizational development in the third millennium; it has economic, social, and direct effects on the rate of access to health services and the quality of such services (19,20). Besides, it is necessary to have a special attention for proper distribution of specialist manpower in the hospitals and other health centers in developing countries to achieve the goals of permanent development (21).…”
Section: Discussionmentioning
confidence: 99%